Assessing motor proficiency in young adults: The Bruininks Oseretsky Test-2 Short Form and the McCarron Assessment of Neuromuscular Development - McIntyre, F.; Parker, H.; Thornton, A.; Licari, M.; Piek, J.; Rigoli, Daniela; Hands, B. (Elsevier BV; North Holland, 2016)
© 2016 Elsevier B.V.Currently, only two motor tests have norms extending into young adulthood - the McCarron Assessment of Neuromuscular Development (MAND, McCarron 1997) and the Bruininks Oseretsky Test of Motor Proficiency-2 (BOT-2, Bruininks & Bruininks, 2005). Research into the motor difficulties in early adulthood and health outcomes has been impeded because there is no agreed gold standard motor test for this group. The purposes of this study were to compare the discrimination accuracy, classification agreement, and predictive values, and gender distribution and prevalence of each test in identifying motor impairment (MI) in relation to DSM-V diagnostic criteria for DCD. Ninety-one young, healthy adults (M = 21.4. years, SD = 3.3) were recruited. Those classified as MI by each test scored at one standard deviation or more below the overall mean standard score. Small, statistically significant correlations were found between the MAND and BOT-2 SF tests for score rank (r = 0.370, . p = 0.01) and standard score values (r = 0.404; p = 0.01). The overall decision agreement for non-MI cases was relatively high at 85% but very low for MI cases (4.4%). Unexpectedly, gender was balanced in MI cases. BOT-2 SF identified twice as many MI cases than MAND (13.2% vs 6.6%), yet overall comparative test specificity was high (89%). Predictive values for MAND, compared against BOT-2 SF as the standard, indicated broad independence between these tests and overall, the decision statistics indicated that the two tests identified different adult cohorts with MI. Objective classification of adult motor proficiency using a gold standard assessment tool including complex and ecologically valid tasks is still elusive.